Analisis Tingkat Adopsi Teknologi dan Dampaknya Terhadap Perkembangan Usaha UMKM Di Kota Gorontalo (Studi Kasus Pada UMKM Binaan Dan Non Binaan) - Moh. Rizki Drajatun; Abdul, Irawati; Rantow Payu, Boby (Jurnal Paradigma Ekonomika, 2026)
This study analyzes the level of technology adoption and its impact on the business development of micro, small, and medium enterprises (MSMEs) in Gorontalo City, Indonesia. Using a quantitative descriptive comparative design, data were obtained from 86 MSMEs 43 assisted and 43 non-assisted through structured questionnaires. The results reveal significant differences in technology adoption levels between the two groups (p < 0.05). Furthermore, the study confirms a strong positive impact of technology adoption on business growth (p < 0.01), where MSM Es with a high level of digital adoption experienced approximately 25–30% higher income growth compared to those with low adoption. These findings emphasize that technological adoption not only distinguishes business performance among MSMEs but also acts as a key driver for income expansion and competitive advantage through digital transformation. These results position technology adoption as both a key differentiator of MSME performance and a vital driver of sustainable growth and competitiveness. Policymakers should prioritize targeted digital training to bridge this gap.